ChemInform Abstract: Mukaiyama—Michael Reactions with trans‐2, 5‐Diarylpyrrolidine Catalysts: Enantioselectivity Arises from Attractive Noncovalent Interactions, Not from Steric Hindrance. Issue 42 (14th October 2014) - Kemppainen, Eeva K.; Sahoo, Gokarneswar; Piisola, Antti; Hamza, Andrea; Kotai, Bianka; Papai, Imre; Pihko, Petri M.
Abstract The 2, 5‐diphenylpyrrolidine‐catalyzed enantioselective Mukaiyama—Michael reaction between substituted furans and enals is studied.